Operation Mincemeat : how a dead man and a bizarre plan fooled the Nazis and assured an allied victory - Macintyre, Ben, 1963- (New York : Harmony Books, 2010)
From the acclaimed author of "Agent Zigzag" comes an extraordinary account of the most successful deception--and certainly the strangest--ever carried out in World War II, one that changed the prospects for an Allied victory. The purpose of the plan--code named Operation Mincemeat--was to deceive the Nazis into thinking that Allied forces were planning to attack southern Europe by way of Greece or Sardinia, rather than Sicily, as the Nazis had assumed, and the Allies ultimately chose.
Includes bibliographical references (p. [385]-387) and index.
Keywords: Montagu, Ewen, -- 1901-1985.; Great Britain. -- Royal Navy -- History -- World War, 1939-1945.; Operation Mincemeat; World War, 1939-1945 -- Secret service -- Great Britain; Deception -- Great Britain -- History -- 20th century; Deception -- Spain -- Atlantic Coast -- History -- 20th century; World War, 1939-1945 -- Spain -- Atlantic Coast; World War, 1939-1945 -- Campaigns -- Italy -- Sicily; Sicily (Italy) -- History, Military -- 20th century; Atlantic Coast (Spain) -- History, Military -- 20th century